การพัฒนาโปรแกรมบูรณาการคณิตศาสตร์กับวิทยาศาสตร์ด้วยวิธีสอนแบบโครงการสำหรับนักเรียนชั้นประถมศึกษาปีที่ 6 ที่มีความสามารถพิเศษทางคณิตศาสตร์ - สุคนธ์ทิพย์ ตาสิงห์ (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
The purpose of this study w as to develop a program integrating mathematics and science using project approach for Prathom Suksa six gifted students in mathematics. The subjects w ere 15 Prathom Suksa six gifted students in m athematics. The method of study consisted of 3 phases; construction, field testing, and revision of the program. The data from the program experimentation in this study were analyzed by using arithmetic mean, standard deviation and t - test. The results w ere a s follows : 1) after using the program, mean score of learning achievement in mathematics and science was significantly higher than before at the .05 level of significance and 2) mean scores of students’ perception concerning the program w ere varied from the moderate level to the highest level. Data from the program experimentation was used for the improvement of the program, and a program integrating mathematics and science using project approach for Prathom Suksa six gifted students in mathematics was presented. The characteristic of this program is an enrichment program for 36 days: 1 hour a day after school. The method of teaching in this program is project approach following 4 phases : 1) introduction to the project 2) project in progress 3) project presentation, and 4) project evaluation.